БЕСИК ЖЫРЛАРЫНЫҢ ЖАНРЛЫҚ ҲӘМ КОМПОЗИЦИЯЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Баўатдинова, С.Ж. (FAN va JAMIYAT, 2023)
The ideological content of performing lullabies is oriented towards the same goals in the nations of the whole world, it is caring for the newborn baby in the family, giving good communication and upbringing in a pleasant environment with kind words for the soul. The Besik song has a certain place in the folk songs created as a genre in itself.